2013
DOI: 10.1021/ci400518g
|View full text |Cite
|
Sign up to set email alerts
|

XenoSite: Accurately Predicting CYP-Mediated Sites of Metabolism with Neural Networks

Abstract: Understanding how xenobiotic molecules are metabolized is important because it influences the safety, efficacy, and dose of medicines and how they can be modified to improve these properties. The cytochrome P450s (CYPs) are proteins responsible for metabolizing 90% of drugs on the market, and many computational methods can predict which atomic sites of a molecule--sites of metabolism (SOMs)--are modified during CYP-mediated metabolism. This study improves on prior methods of predicting CYP-mediated SOMs by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
246
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 192 publications
(253 citation statements)
references
References 21 publications
2
246
0
Order By: Relevance
“…The bulk of our descriptors have been previously shown to be useful for the XenoSite metabolism model, although we supplement them with new reactivity descriptors in the current study. 12 Several of these descriptors have been proposed as reactivity indices, such as the energies of the lowest unoccupied and highest occupied molecular orbitals ( E LUMO and E HOMO ), the maximum nucleophilic and electrophilic delocalizabilities (max[ D N ( r )] and max[ D E ( r )]), and the maximum self-polarizability (max[ π S ( r )]). Moreover, D N ( r ), D E ( r ), and π S ( r ) have been proposed as atom-level reactivity indices that may predict sites of GSH reactivity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of our descriptors have been previously shown to be useful for the XenoSite metabolism model, although we supplement them with new reactivity descriptors in the current study. 12 Several of these descriptors have been proposed as reactivity indices, such as the energies of the lowest unoccupied and highest occupied molecular orbitals ( E LUMO and E HOMO ), the maximum nucleophilic and electrophilic delocalizabilities (max[ D N ( r )] and max[ D E ( r )]), and the maximum self-polarizability (max[ π S ( r )]). Moreover, D N ( r ), D E ( r ), and π S ( r ) have been proposed as atom-level reactivity indices that may predict sites of GSH reactivity.…”
Section: Methodsmentioning
confidence: 99%
“…32 We found success with this approach when predicting P450 metabolism. 12 When applied in this study, the strategy was capable of encoding nonlinear relationships and simultaneously making SOR predictions for each atom in a molecule along with GSH reactivity predictions for the molecule as a whole. The validation of those models demonstrated the ability to model effectively GSH reactivity of diverse chemicals, both identifying reactive molecules and sites of reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal algorithm will rank a sufficient number of active compounds before the inactives, but the rankings of actives relative to other actives and inactives are less important [384]. Computational modeling also has the potential to predict ADMET traits for lead generation [385] and how drugs are metabolized [386].…”
Section: Ligand-based Prediction Of Bioactivitymentioning
confidence: 99%
“…A study of 22 ADMET tasks demonstrated that there are limitations to multi-task transfer learning that are in part a consequence of the degree to which tasks are related [385].…”
Section: Ligand-based Prediction Of Bioactivitymentioning
confidence: 99%
See 1 more Smart Citation